The Title in Samples of Contemporary Arabic Grammatical Studies: A Critique of the Foundations of Grammatical Classification - recen, ahmed (El Omda in Linguistics and Discourse Analysis, 2018)
The researcher does not intend to impose logical thinking and its intellectual precision on grammatical studies, because grammatical research does not possess the logical infallibility dictated by formal logic. The nature of a normative science does not fall under the umbrella of exact sciences, no matter how diligently the researcher strives for it. This is because the linguistic nature is influenced by the complex desires and inclinations of humans, which significantly affect their mental dimension. However, this incidental influence does not prevent researchers from benefiting from the science of logic, as it safeguards against errors in general reasoning when applied to correct the course of their studies and directs their grammatical thinking toward useful outcomes in modern grammatical analysis.